The Role of Waqf as a Pillar of Social and Economic Development for Muslims - Ismail; Ahmad Riyansyah; Salisa Amini (Journal of Global Islamic Economic Studies, 2024)
Waqf is one of the sharia financial instruments that has great potential in supporting the social and economic development of Muslims in a sustainable manner. This research aims to explore the strategic role of waqf in strengthening the welfare of the people through the provision of public services, poverty reduction, and community economic empowerment. Using a descriptive qualitative approach and literature study, this study analyzes various literature and scientific journals related to waqf management, both traditional and modern. The results of the study show that waqf not only functions as a charity of worship, but also as a mechanism for fair and sustainable distribution of wealth. In practice, waqf is able to finance the education, health, and infrastructure sectors, while supporting productive economic sectors that create jobs and increase people's income. However, optimizing the role of waqf still faces various challenges, such as weak governance, low public literacy, and lack of synergy between regulators and waqf management institutions. Therefore, reform of waqf management based on technology and the principles of good governance is a necessity. This study concludes that waqf can be the main pillar in the development of Muslims if it is managed professionally, transparently, and collaboratively. The novelty of this research lies in the integrative approach between the social and economic functions of waqf which is comprehensively studied, by emphasizing the importance of information technology-based management and modern governance in facing the challenges of contemporary Muslim development.